A Modified Odenthal Rollover Index Algorithm For Tractor-Semitrailer Using Steering And Vehicle Speed Inputs - Harun, Mohamad Hafiz; Hudha, Khisbullah; Mohd Samin, Pakharuddin; Abu Bakar, Saiful Anuar; Amer, Noor Hafizah; Abd Kadir, Zulkiffli (Inderscience Publishers, 2021)
One of the main factors that cause tractor-semitrailer accidents is vehicle rollover instability. Therefore, an early warning indicator of an impending vehicle rollover is essential, especially to the tractor-semitrailer driver in order to control the vehicle and eventually avoid the road accident. In this study, the rollover index algorithm is proposed by integrating the modified Odenthal rollover index (MORI) algorithm with driver steering and vehicle speed inputs instead of lateral acceleration. The MORI algorithm performance is evaluated by conducting the experiment involving the step-steering manoeuvres, subjected to various speeds and load conditions in the TruckSim driving simulator and MATLAB/Simulink software. It is observed from the experiment results that the MORI algorithm produced 12.4% faster time-to-warn (TTW) than Odenthal rollover index for the driver and offers adequate time-to-respond (TTR) to initiate the corrective actions. Thus, the MORI algorithm proposed a better early warning system and can prevent rollover accident significantly.